Pengaruh Disrupsi Teknologi terhadap Kompetensi Akuntan dengan Praktik Akuntansi sebagai Variabel Intervening - Wibnu Yafi Wahidin (Journal of Trends Economics and Accounting Research, 2024)
This study aims to measure the effect of technological disruption on accountant competence and the effect of accounting practices mediating the effect of technological disruption on accountant competence. The method and analysis technique used is a quantitative method with 100 Likert-scale questionnaire respondents, and the data analysis used is Structural Equation Modeling which consists of outer model and inner model analysis. The findings of this study state that technological disruption has a significant positive effect on accountant competence with a path coefficient value of 0,192 and p-values of 0,008, technological disruption has a significant positive effect on accounting practices with a path coefficient value of 0,510 and p-values of 0,000, accounting practices have a significant positive effect on accountant competence with a path coefficient value of 0,643 and p-values of 0,000, and technological disruption has a significant positive effect on accountant competence through mediation from accounting practices with a path coefficient value of 0,328 and p-values of 0,000.